Bargaining merger terms and the effect on the announcement returns - Pereira, Paulo J. (2019)
This paper develops a dynamic model for the timing and terms of mergers. In contrast to other models, we show that firms agree about the timing independently from how the merger surplus is shared or their bargaining power. We show that, under asymmetry of information, the combination of surprises on the merger timing and the merger terms, can produce negative or positive abnormal announcement returns for the merging firms. The abnormal returns are also possible under perfect information, even if the announcements are expected by the market, and occur as a result of the event-study methodology.